PAIRED TECHNOLOGIES IMPLEMENTATION TO ENHANCE EFL STUDENT’S WRITING SKILL - Aminatus Sa'diyah (JP : JURNAL PENDIDIKAN, 2020)
ABSTRACT; The pandemic of COVID-19 has forced educational institutions to move their teachings online around the world. As the Indonesian Government released SK Mendiknas No. 107/U/2001, educational institutions had to constantly merge their learning process with technology. So, this research aims to measure the effectiveness of students' writing skills through paired technologies, such as WhatsApp, Facebook, and the video conference as a learning technique to develop students' writing skills. The method used in this research was pre-experimental testing of pre-test and post-test configurations in a single group. The subjects of research consisted of 20 students from the EFL's first high school who were involved in a census sampling methodology. The data were collected utilizing a written exam. The data study shows a large improvement in the total student output in English writing. The mean student pre-test score was 65.30, while the mean student post-test score was 78.05. The t-table was also smaller than the t-test, i.e. 2,093<6,04. Based on the results, the researchers hypothesized that the use of paired technology; the combination of teaching tools in English learning increased the ability of EFL students to write. Keywords; Writing, technology, collaborative tool, EFL students, social media